Catheter-related bacteremia caused by Kocuria salsicia: The first case. Issue 4 (April 2015) - Sohn, Kyung Mok; Baek, Jin-Yang; Kim, So Hyun; Cheon, Shinhye; Kim, Yeon-Sook
Abstract: We report the first case of catheter-related bacteremia caused by Kocuria salsicia in a patient with short bowel syndrome. The pathogen was initially identified as Kocuria varians by a Vitek 2-based assessment, but its 16S rRNA gene sequence showed 100% similarity to K. salsicia . The patient was successfully treated with vancomycin and removal of the catheter.